Pengembangan Sistem IT Helpdesk Berbasis Android Di Disaster Recovery Center Kospin Jasa Purbalingga - Fadlilah, Nuzul Imam; Widodo, Pudji; Hidayatulloh, Toip (J-INTECH (Journal of Information and Technology), 2023)
A helpdesk is an area or department in a company that carries out the process of collecting data from various existing sources and must actively listen and respond to user needs. It is hoped that the development of the Helpdesk will be able to overcome various problems and provide extensive services for internal and operational problems, as well as problems related to information systems and technology. The Information Technology Helpdesk system at the Kospin Jasa Purbalingga Disaster Recovery Center currently only uses manual writing, telephone, and the Android application, namely WhatsApp. If a problem occurs related to IT devices, the user immediately contacts IT via telephone or WhatsApp. The Helpdesk application can reduce data processing time, reduce human error in the data recording process, and produce helpdesk reports quickly and accurately, to support the company's decision-making process. The research method used is the analytical method. The analysis used is problem identification, test scenario analysis, system requirements analysis, hardware requirements analysis, software requirements analysis, and HR requirements analysis.